KORELASI ANTARFAKTOR KEPUASAN KERJA PUSTAKAWAN: STUDI KASUS PUSTAKAWAN LEMBAGA ILMU PENGETAHUAN INDONESIA - Kusumaningrum, Dwiatri; Yudhanto, Seno; Yoganingrum, Ambar (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2016)
Librarian job satisfaction is influenced by a number of factors, among others, the working environment, motivation, and compensation. Knowing the relationship between these factors will be helpful for the improvement of job satisfaction, which in turn will improve the professionalism of librarians. This study aims to measure the correlation between these factors. Respondents are librarians within Indonesian Institute of Science, with the post of librarian executing, implementing advanced, supervisors, first, the young and middle. Collecting data using questionnaires, while the correlation measurement using the method of Kendal and Spearman. The study results show that there is no significant relationship between work environment factors and compensation as well as among the factors of motivation and compensation.